Pengaruh Konsentrasi Tween 80 Terhadap Karakteristik Serbuk Pewarna Daun Singkong (Manihot utilissima Pohl.) Pada Metode Foam Mat Drying - Prisceilla Isabella, Debora; Diah Puspawati, Gusti Ayu Kadek; Sri Wiadnyani, Anak agung Istri (Jurnal Ilmu dan Teknologi Pangan (ITEPA), 2022)
Cassava leave is one type of leaf that has high chlorophyll so it can be used as a natural green dye, but using of it was still limited and needs to develop. This study aimed to determine the effect of the concentration of tween 80 on the characteristic of the pigment powder of cassava leave on foam mat drying method and to proper concentration of tween 80 to get the pigment powder of cassava leave with the best characteristic on foam mat drying method. The research design used was a Completely Randomized Design (CRD) with tween 80 concentration treatment consisting of 5 levels (0%; 0.5%; 1%; 1.5%; 2%). The experiment was repeated three times to obtain 15 experimental units. The data obtained were analyzed by the analysis of variance and if the treatment had a significant effect to variable observed, it was continued with Duncan’s Multiple Range Test. The parameters observed in this study included: yield, moisture content, total chlorophyll, solubility and L*, a*, b* values. The results showed that the concentration of tween 80 had a significant effect (P<0,05) on yield, moisture content, total chlorohyll, solubility and L*, a*, b* values. The best treatment was obtained at a concentration level of tween 80 at 1.5% with characteristic: yield of 11.51%, moisture content of 2.08%, total chlorophyll of 6.87 mg/g, solubility of 85.47%, the L* value of 11.53, the a* value of -38.30, and the b* value of 15.83.